TERRITORIAL DIVERSITY RESEARCH TRENDS WITHIN THE CONTEXT OF AGRICULTURAL POLICY - Roxana FRANZUTTI; Alexandru FINTINERU; Dragos SMEDESCU; Gina FINTINERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Common Agricultural Policy (CAP) represents not only one of the most important EU policy, holding a large share of overall EU funds, but is also one of key drivers of EU rural spatial development. It is important therefore, to look into its impact and how it can best respond to the specific challenges for agriculture and rural areas. There is an increasing number of studies on the CAP impacts on the farming indicators such as agricultural production efficiency, employment, profitability, structural issues. However, very little attention has been paid to territorial diversity among rural areas in each country. The main aim of this paper is to examine the existent situation of the topic researches conducted at EU level between 1994-2020 regarding the CAP, taking into account the territorial diversity. By analysing the current literature through Web of Science and Science Direct scientific databases we were able to obtain information on the research topic previously mentioned from several perspectives, using a list of predetermined key words, starting from “territorial diversity”. The conclusions drawn from our study will serve as support in creating an analysis at the Romanian level regarding the implementation of the CAP.